1963
DOI: 10.1139/y63-219
|View full text |Cite
|
Sign up to set email alerts
|

End Group and Sedimentation Data on Fragmented High Molecular Weight Ribonucleates

Abstract: A method for end group analysis of ribonucleate preparations using purified snake venom phosphodiesterase is described. Unusual difficulties encountered with the method are discussed. The technique is useful for detection of end groups resulting from enzymic and chemical fragmentation of high molecular weight ribonucleates. Preliminary studies indicate that the method has limited usefulness because of a spontaneous hydrolysis of ribonucleates which occurs under the conditions which are optimal for hydrolysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1964
1964
1969
1969

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Evidence has been presented in previous publications (12,13) which showed that the chain ends detected as rlucleosides and diphosphonucleosides after Can. J. Biochem.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Evidence has been presented in previous publications (12,13) which showed that the chain ends detected as rlucleosides and diphosphonucleosides after Can. J. Biochem.…”
Section: Resultsmentioning
confidence: 71%
“…The end groups detected in IS S + 2S S ribonucleates by hydrolysis with purified snake venom phosphodiesterase are probably formed, in large part, as the result of spontaneous hj~droxyl ion catal~yzed cleavages during the analysis itself. The lonr recoverJr of nucleoside diphosphates in phosphodiesterase digests could reflect 21 partial destruction and poor recovery of these compounds in such digests (13,13), and it is therefore nlandatory to base estimates of minimal chain length on analysis for the type of chain end which is linked by a phosphodiester bridge to its 3' position. The latter chain termini are not subject to an!-known destruction after release by alkali or phosphodiesterase hydrolysis, and appear cluantitatively as nucleosides in phosphodiesterase digests if they do not bear pliospliomonoester groups and appear quantitatively as nucleoside diphosphates in alkali hyclrolj~zates if they bear a phosphornonoester group at the 5' position.…”
Section: Resultsmentioning
confidence: 99%
“…Isolation of 5-Carboxymethyluridine 5'-Phosphate from tRNA. To check the possibility that 5-carboxymethyluridine might be present as the free carboxylic acid in tRNA, wheat embryo tRNA was hydrolyzed with purified snake venom phosphodiesterase under conditions that achieve complete hydrolysis of the RNA (Lane et al, 1963;Hudson et al, 1965). The hydrolysis products were fractionated on DEAE-cellulose according to net charge at pH 7.8, and the fraction which eluted after the 5'-nucleotides was examined to determine if it contained any 5-carboxymethyluridine 5'-phosphate.…”
Section: Resultsmentioning
confidence: 99%
“…The developing solvents were 9 5 z ethyl alcohol-water (4:1, v/v) (system 1) and saturated ammonium sulfate-2-propanol (40: 1, v/v) (system 2); they were used in conjunction with Whatman No. 1 chromatography paper which had been impregnated with ammonium sulfate (Lane, 1963).…”
Section: Methodsmentioning
confidence: 99%
“…The first problem can be solved by methods that give nuclease-free preparations such as that ofCox & Arnstein (1963). For terminalgroup analysis non-radioactive techniques (Lane, Diemer & Blashko, 1963) require amounts of about 50pug. of the terminal nucleoside, thus requiring 150mg.…”
mentioning
confidence: 99%